Comparing optical quality and simulated defocus curves: head-to-head analysis of hydrophilic and hydrophobic trifocal intraocular lenses - Łabuz, Grzegorz; Yan, Weijia; Khoramnia, Ramin; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2025)
PURPOSE: To examine the optical function of the new AT ELANA trifocal intraocular lens (IOL) made of hydrophobic material against an equivalent version made of hydrophilic material. - SETTING: David J Apple Center for Vision Research, Heidelberg, Germany. - DESIGN: Laboratory investigation. - METHODS: This optical investigation was conducted on +20 diopter (D) samples of the AT ELANA and AT LISA tri. The area under the modulation transfer function (MTFa) served as a quality criterion. Simulated visual acuity (VA) and defocus curves across +1 to -3.5 D range were derived from an empirical formula according to ANSI Z80.35. Susceptibility to photic phenomena was evaluated by assessing the light distribution around a point light source. - RESULTS: The 2 models demonstrated comparable optical quality. While at distance, a 4% improvement was noted with the AT LISA tri, the AT ELANA's near MTFa was 5% higher. Only a marginal difference (1%) was noted at intermediate. Both IOLs reached simulated VA of 0.0 logMAR far vision, 0.10 logMAR at 80 cm, and 0.05 logMAR at 40 cm. Still, the near range was slightly expanded with the hydrophobic model. The light-spread profile was comparable between the 2 trifocals. - CONCLUSIONS: The AT ELANA and AT LISA tri demonstrated comparable optical quality and similarities in the potential for inducing photic phenomena. This study suggests that the hydrophobic trifocal IOL may provide visual range comparable with its hydrophilic counterpart. However, the asphericity change may facilitate the selection of a model that more effectively addresses specific corneal aberrations.